PERCEPTION AND MOTIVATION OF STUDENTS TOWARDS PROJECT-BASED LEARNING (PJBL) IN LANGUAGE LEARNING - Indrayani, Septina; Farizka Humolungo; Dewi Kurniawati (Politeknik Negeri Jakarta, 2024)
Project-based learning (PjBL) has emerged as a prominent approach in vocational education, particularly in language learning, as it aligns closely with the challenges of the professional world. This study investigates the perceptions and motivations of vocational students toward the implementation of PjBL in their language courses. The purpose of this study is to analyze students' experiences with PjBL, identify the factors influencing their motivation and engagement, and propose recommendations for improving the effectiveness of PjBL in vocational education. A mixed-method approach was employed, combining quantitative data from structured questionnaires completed by 170 students across three semesters and qualitative insights from Focus Group Discussions (FGD). The sampling technique ensured representation from students with varying levels of experience with PjBL. The findings show that in general, students perceive PjBL positively, recognizing its role in enhancing their understanding of course material and developing critical skills such as communication and collaboration. However, challenges such as inconsistent instructions from lecturers, tight deadlines, and a lack of focus on the learning process in assessments were noted as significant barriers to engagement and motivation. PjBL holds substantial promise for improving language learning outcomes in vocational education. By addressing instructional consistency, providing flexible timelines, and emphasizing formative assessments, PjBL can be further optimized to better prepare students for the demands of their future careers.